Pengaruh Konsumsi Fast Food, Asupan Sarapan Pagi dan Aktivitas Fisik terhadap Kejadian Obesitas pada Remaja Putri - Rilla Simpati; Retno Sugesti (SIMFISIS Jurnal Kebidanan Indonesia, 2021)
Introduction: Obesity has become a worldwide epidemic health problem. The World Health Organization (WHO) states that more than 1.9 billion adults aged 18 years and over are overweight and 600 million of them are obese. In 2014 an estimated 41 million children under the age of 5 are obese. Objectives: aiming to determine the effect of the influence of fast food consumption, breakfast intake and physical activity on the incidence of obesity in adolescent girls at the Bekasi 13th high school in 2019. Method: This study uses the Stuctural Equation Modeling (SEM) method with the Crossapproach Sectional. The total population in this study was 118 respondents, the determination of the number of samples that were reseventative with a total sample of 70 respondents taken using accidental sampling technique. The research instrument was tested for validity and reliability testing, the instrument used in this study was a questionnaire. Result: The results in this study there is a direct effect of fast food consumption on the incidence of obesity (9.45%, T Statistic 4.06%, α 5%), there is a direct effect on breakfast intake on the incidence of obesity (4.04%, T Statistic 3, 04%, α 5%), there is a direct influence of physical activity on the incidence of obesity (5.00%, Statistical T value 2.67% α 5%). Conclution: The conclusion is there is the influence of fast food consumption, breakfast intake and physical activity on the incidence of obesity in adolescent girls in Bekasi 13th High School in 2019. The suggestion is expected that adolescents reduce consuming fast food so that health is maintained and prevent obesity.